Hybrid photoelectrochemical and photovoltaic cells for simultaneous production of chemical fuels and electrical power. Issue 12 (December 2018) - Segev, Gideon; Beeman, Jeffrey; Greenblatt, Jeffery; Sharp, Ian
Abstract Harnessing solar energy to drive photoelectrochemical reactions is widely studied for sustainable fuel production and versatile energy storage over different timescales. However, the majority of solar photoelectrochemical cells cannot drive the overall photosynthesis reactions without the assistance of an external power source. A device for simultaneous and direct production of renewable fuels and electrical power from sunlight is now proposed. This hybrid photoelectrochemical and photovoltaic device allows tunable control over the branching ratio between two high-value products of solar energy conversion, requires relatively simple modification to existing photovoltaic technologies, and circumvents the photocurrent mismatches that lead to significant loss in tandem photoelectrochemical systems comprising chemically stable photoelectrodes. Our proof-of-concept device is based on a transition metal oxide photoanode monolithically integrated onto silicon that possesses both front- and backside photovoltaic junctions. This integrated assembly drives spontaneous overall water splitting with no external power source, while also producing electricity near the maximum power point of the backside photovoltaic junction. The concept that photogenerated charge carriers can be controllably directed to produce electricity and chemical fuel provides an opportunity to significantly increase the energy return on energy invested in solar fuels systems and can be adapted to a variety of architectures assembled from different materials. Solar energy is widely used for fuel production and energy storage, but the majority of photoelectrochemical cells cannot operate without an external power source. A device for simultaneous and direct production of renewable fuels and electrical power is now proposed.